Economic impact of delirium in Australia: a cost of illness study - Gideon A Caplan; Andrew Teodorczuk; Lynne Pezzullo; Jared Streatfeild; Josiah Hickson; Meera R Agar (BMJ Open)
Objectives To estimate the economic impact of delirium in the Australian population in 2016–2017, including financial costs, and its burden on health.Design, setting and participants A cost of illness study was conducted for the Australian population in the 2016–2017 financial year. The prevalence of delirium in 2016–2017 was calculated to inform cost estimations. The costs estimated in this study also include dementia attributable to delirium.Main outcome measures The total and per capita costs were analysed for three categories: health systems costs, other financial costs including productivity losses and informal care and cost associated with loss of well-being (burden of disease). Costs were expressed in 2016–2017 pound sterling (£) and Australian dollars ($A).Results There were an estimated 132 595 occurrences of delirium in 2016–2017, and more than 900 deaths were attributed to delirium in 2016–2017. Delirium causes an estimated 10.6% of dementia in Australia. The total costs of delirium in Australia were estimated to be £4.3 billion ($A8.8 billion) in 2016–2017, ranging between £2.6 billion ($A5.3 billion) and £5.9 billion ($A12.1 billion). The total estimated costs comprised financial costs of £1.7 billion and the value of healthy life lost of £2.5 billion. Dementia attributable to delirium accounted for £2.2 billion of the total cost of delirium.Conclusions These findings highlight the substantial burden that delirium imposes on Australian society—both in terms of financial costs associated with health system expenditure and the increased need for residential aged care due to the functional and cognitive decline associated with delirium and dementia. To reduce the substantial well-being costs of delirium, further research should seek to better understand the potential pathways from an episode of delirium to subsequent mortality and reduced cognitive functioning outcomes.